Congenital radioulnar synostosis - Yammine, K. (1998)
The authors report a retrospective series of 37 patients (49 forearms) with congenital radioulnar synostosis followed and treated at Raymond Poincaré University Hospital. This disease is rare, but much more frequent than post-traumatic or humeroradial synostosis. A genetic factor was incriminated in 25% of patients. The clinical study was based on 31 files (40 forearms) with a subjective finding of hypermobility of the wrist in all patients. Shortening of the ipsilateral upper extremity ≤ 2 cm was also observed in one third of patients, and a defect of elbow extension was observed in 35%. The radiological study, conducted on 30 files (38 forearms), confirmed the existence of several degrees of fusion within the synostosis and revealed an associated radiological abnormality in 92% of cases. The only valid correlation revealed was between the degree of fusion of the synostosis and the presence of a morphological abnormality of the radial head (r = 0.87), hence the proposal of a new radiological classification essentially based on this element. Functional adaptation was excellent in the majority of cases. The authors propose two main indications for surgery : hyperpronation ≥ 90° and bilateral synostosis; in both cases, the disability must be very severe. The operative technique used appeared to be very well adapted to this disease : « reedradial osteotomy and transverse ulnar osteotomy. No complications or relapses were observed in six operated patients with a mean follow-up of 10 years, with a mean loss of derotation of only 5°.